2x-y=4

Subtract 2x from both sides of the equation.

-y=4-2x

Multiply each term in -y=4-2x by -1

Multiply each term in -y=4-2x by -1.

(-y)⋅-1=4⋅-1+(-2x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=4⋅-1+(-2x)⋅-1

Multiply y by 1.

y=4⋅-1+(-2x)⋅-1

y=4⋅-1+(-2x)⋅-1

Simplify each term.

Multiply 4 by -1.

y=-4+(-2x)⋅-1

Multiply -1 by -2.

y=-4+2x

y=-4+2x

y=-4+2x

y=-4+2x

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=-4+2(0)

Simplify -4+2(0).

Multiply 2 by 0.

y=-4+0

Add -4 and 0.

y=-4

y=-4

Use the x and y values to form the ordered pair.

(0,-4)

(0,-4)

Remove parentheses.

y=-4+2(1)

Simplify -4+2(1).

Multiply 2 by 1.

y=-4+2

Add -4 and 2.

y=-2

y=-2

Use the x and y values to form the ordered pair.

(1,-2)

(1,-2)

Remove parentheses.

y=-4+2(2)

Simplify -4+2(2).

Multiply 2 by 2.

y=-4+4

Add -4 and 4.

y=0

y=0

Use the x and y values to form the ordered pair.

(2,0)

(2,0)

These are three possible solutions to the equation.

(0,-4),(1,-2),(2,0)

Find Three Ordered Pair Solutions 2x-y=4